Land Property Market Value Determination Database for Collateral Purpose (Case Study: PT. Bintang Dharma Hurip Pekanbaru) - Qurrotul Aini; Bakri La Katjong; Vicy Adriani (International Journal of Electrical and Computer Engineering (IJECE), 2011)
PT. Bintang Dharma Hurip, as one of appraisal companies already has the land and residential data in Pekanbaru, many data were not stored in organized database, therefore made difficult and delayed tasks of valuer especially to determine the Reproduction Cost New (RCN). The problem would be resolved when researchers proposed a dynamic property database, calculated the market value of land and implementation fuzzy queries so the redundancy data and loss can be minimized. The purpose of the research was to obtain a reference database application of properties in Pekanbaru based on last two years survey by PT. Bintang Dharma Hurip. The development method of research used Rapid Application Development, which were consists of requirements, design, construct, and implementation phases. The application used Visual Basic 6.0 and Microsoft Access 2003 as database tools. The research result was a database application size 6 MB. The user’s application divided into three, which are inspector, valuer, and reviewer. In the implementation phase, the researcher asked three reviewers, two valuers and one inspector PT. Bintang Dharma Hurip to conduct tests on the application. Apparently, from the test results, researchers concluded that the application is running well and suitable with company’s needs. Keywords: database, fuzzy, property, market value, PT. Bintang Dharma Hurip.DOI:http://dx.doi.org/10.11591/ijece.v1i1.62